Innovative foundations for optimizing the information and communication system of local government - Diegtiar, Oleg A.; Kravchenko, Тetyana A.; Yevmieshkina, Olena L.; Sych, Tetiana V.; Linetska, Yana M. (Linguistics and Culture Review, 2021)
The article is devoted to the study of innovative methods of optimizing the information and communication system of the local government of Ukraine in the changing conditions of nowadays. The main problem of the article is due to the need to eliminate the inconsistency of the modern unsatisfactory state of development of information support for the provision of public services by local self-government bodies of the territories of Ukraine with the requirements of Ukrainian society and the standards of European developed countries. The definition of the category “innovative municipal administration” has been clarified. Specific features of public service provision are defined according to four criteria (“service provision,” “restrictions,” “service concentration,” “monopoly of services”), which disclose their essence and main areas of improvement. The author's definition of the category “public service” is given. It was found that effective servicing of the needs of civil society and economic entities is impossible without the involvement of information systems and technologies and requires the implementation of systematic information support for the management and service activities of local self-government bodies. An innovative information and communication system has been formed to ensure the activities of local self-government bodies in the provision of public services.